A new method for extracting the insoluble occluded carbon in archaeological and modern phytoliths: Detection of 14C depleted carbon fraction and implications for radiocarbon dating. (February 2017) - Asscher, Yotam; Weiner, Steve; Boaretto, Elisabetta
Abstract: Phytolith-rich layers in archaeological sites constitute well defined stratigraphic horizons that would be invaluable if absolutely dated. Previous attempts to radiocarbon date phytoliths produced inconsistent results using plants with known ages. In this study a new approach to extract and analyze the silica occluded carbon was tested on well-dated archaeological contexts in Beth Shemesh and Tell es-Safi/Gath, and on modern wheat plants that grew in a controlled environment. Results show that by dissolving the silica using mild conditions, phytolith insoluble fractions can be extracted and their radiocarbon contents analyzed reproducibly. After phytolith dissolution, the remaining insoluble fractions with 10–30%C have radiocarbon concentrations that are statistically similar to associated charred seeds (within 2σ), and insoluble fractions with 40%C show concentrations that are identical to the seeds. These results show that the insoluble fraction of phytoliths is a suitable material for answering chronological questions. Highlights: This research will be of large interest for the archaeological community, the phytolith community and also the radiocarbon dating community. Our results indicate that archaeological phytoliths can be radiocarbon dated, but strict control on the pre-treatment parameters is fundamental.